Transnationalization of internal financial markets economy and forming - Кулай, Аліна Василівна; Kulaj, A. V. (My University, 2016)
In the article the influence of globalization on transnational business as an integral part of the micro level component of economic space is reviewed The essence of infernal financial markets as a main source of foreign direct investment was revealed. The stages of formation and development of multinationals were investigated. В статті розглянуто вплив процесів глобалізації на транснаціональний бізнес, як невід’ємну складову мікрорівневого компоненту економічного простору. Розкрито сутність інтернальних фінансових ринків – основного джерела прямих іноземних інвестицій. Досліджено етапи становлення та розвитку ТНК .
Транснаціоналізація економіки і формуванння інтернальних фінансових ринків
Keywords: транснаціональні компанії; інтернальний фінансовий ринок; глобалізація; multinational companies; internal financial market; globalization